A developer's guide to the semantic web - Liang, Yu (Springer, 2011)
Covering the theory, technical components and applications of the Semantic Web, this book's unrivalled coverage includes the latest on W3C standards such as OWL 2, and discusses new projects such as DBpedia. It also shows how to put theory into practice